Magnonic Key Based on Skyrmion Clusters - Escrig-Murua, J; Saavedra-Díaz, E (Nature Research, 2021)
In this work, we report the excitation of spin-waves modes in skyrmion clusters hosted in Co/Pt nanodots by applying an in-plane magnetic field pulse. The direction at which the magnetic field is applied enables the excitation of five main spin-waves modes that are understood in terms of only azimuthal-like modes, which are shown to be strongly dependent on the number of skyrmions stabilized in the system. This feature converts the present system in a mechanism to activate and suppress a set of given modes, which in turn we propose to be utilized as a magnonic key based skyrmion cluster. Our results could be useful in manufacturing potential magnonic logic devices based in skyrmionic textures. © 2021, The Author(s).